Distribusi frekuensi manifestasi oral pada penderita penyakitAutoimun rheumatoid arthritis - Marcel Santoso, Andreas; Nova Fitri, Andrian; Kelsi Hartanto, Firstine; Goalbertus (Jurnal Kedokteran Gigi Terpadu, 2024)
Rheumatoid arthritis is an autoimmune disease that often occurs in Indonesian society, especially in the elderly. As the results in RISKESDAS in 2018, the percentage of Indonesian people affected by joint diseases including rheumatoid arthritis is 7.30%. According to WHO (2016) rheumatoid arthritis affects 20% of the general population. Indonesia as an industrialized country has a higher prevalence of rheumatoid arthritis autoimmune disease, which is 2%.